2007
DOI: 10.1158/1541-7786.mcr-06-0395
|View full text |Cite
|
Sign up to set email alerts
|

Gα12/13 Basally Regulates p53 through Mdm4 Expression

Abstract: GA 12/13 , which belongs to the GA 12 family, participates in the regulation of diverse physiologic processes. In view of the control of GA 12/13 in cell proliferation, this study investigated the role of GA 12/13 in the regulation of p53 and mdm4. Immunoblotting and immunocytochemistry revealed that p53 was expressed in control embryonic fibroblasts and was largely localized in the nuclei. GA 12 deficiency decreased p53 levels and its DNA binding activity, accompanying p21 repression with Bcl 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 58 publications
(82 reference statements)
1
8
0
Order By: Relevance
“…Preliminary experiments showed that Nrf2 responsiveness to a prooxidant in RK Ϫ/Ϫ cells was identical to that of wild-type (WT) MEFs or hepatocyte-derived cells (HepG2 and H4IIE). We also reported that the G␣ 12 dependent gene expression pattern in RK Ϫ/Ϫ cells was identical to that in WT cells (26,27). Nrf2 levels were minimal in the nuclear fraction of RK Ϫ/Ϫ cells but high in that of G␣ 12 Ϫ/Ϫ cells (Fig.…”
Section: Resultssupporting
confidence: 61%
“…Preliminary experiments showed that Nrf2 responsiveness to a prooxidant in RK Ϫ/Ϫ cells was identical to that of wild-type (WT) MEFs or hepatocyte-derived cells (HepG2 and H4IIE). We also reported that the G␣ 12 dependent gene expression pattern in RK Ϫ/Ϫ cells was identical to that in WT cells (26,27). Nrf2 levels were minimal in the nuclear fraction of RK Ϫ/Ϫ cells but high in that of G␣ 12 Ϫ/Ϫ cells (Fig.…”
Section: Resultssupporting
confidence: 61%
“…The transfected cells were subjected to in vitro invasion and transwell migration assays. * Statistically different at P \ 0.01 level of p53 and its DNA-binding activity in mouse embryonic fibroblasts, and G a12 QL-and G a13 QL-promoted p53 accumulation in MCF10A cells [27]. We conducted the subsequent experiments to investigate the involvement of p53 in MMP-2 transcriptional activation by G a12/13 .…”
Section: Resultsmentioning
confidence: 99%
“…Small-interfering(si) RNAs: Knockdown of MMP-2, G a12/13 and p53 was performed [22,27] with siRNA molecules targeting MMP-2(Invitrogen, [28]), p53, G a12 or G a13 (Santa Cruz, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Equally interesting, certain members of the G␣ protein superfamily have been recently shown to regulate p53 expression under nongenotoxic conditions. 23 One limitation of this study is that knockdown of p66shc was not limited to the endothelium. Therefore, although our findings strongly suggest that, in the context of pressor doses of Ang II, endothelial p66shc is the principal mediator of vasomotor dysfunction, we cannot completely exclude the role of p66shc expressed in the vascular smooth muscle and adventitial layers.…”
Section: Discussionmentioning
confidence: 98%